A bibliometric analysis of game-based collaborative learning between 2000 and 2019. (23rd December 2021) - Chen, Xieling; Zou, Di; Xie, Haoran; Cheng, Gary; Su, Fan
This study examined a total of 296 articles on Game-Based Collaborative Learning (GBCL) published between 2000 and 2019 by using bibliometric analysis and mapping methodologies to present the current situation and trends of GBCL research. The papers were analysed from the influential scientific work, authors, institutions, countries/regions and frequently discussed issues in the past 20 years. The bibliometric mapping and keyword analysis highlighted several important changes and future trends of the GBCL research. Based on the results, scholars are encouraged to pay more attention to analysing dialogues and interaction in GBCL to understand learners' behaviour patterns. They are also recommended to continue applying various innovative technologies, such as mobile devices and virtual reality, to facilitate GBCL. The findings obtained provide meaningful implications for the future development of GBCL research.